The Good Manager: Development and Validation of the Managerial Interpersonal Skills Scale - Beenen, Gerard; Pichler, Shaun; Livingston, Beth; Riggio, Ron (Frontiers in Psychology, 2021)
It is no secret that employees leave their organizations because of bad managers- but what about the good ones? How can researchers and organizations differentiate individuals in terms of the interpersonal skills needed to perform well in the managerial role? Although these are fundamentally important questions to organizational psychologists, there exists no conceptual model, definition, or measure of interpersonal skills specific to the managerial role. We address these questions and research gaps by developing a conceptual model and validating a concomitant measure of managerial interpersonal skills (MIPS) through a research program that included four studies across three phases: First, through a review of the literature and structured interviews with practicing managers; next, three quantitative studies in which we develop, refine and validate our MIPS scale; and finally, in a fourth validation study with matched supervisor-employee data from a large healthcare organization. Results suggest that MIPS are best represented by a three-dimensional model comprised of supporting, motivating and managing conflict all indicating a higher-order latent MIPS factor. Results also indicate the MIPS Scale predicts job attitudes and performance among both employees and managers above and beyond personality traits and leader-member exchange, as well as constructs closely related to MIPS, such as social support and conflict management style.